The Cambridge handbook of copyright in street art and graffiti / edited by Enrico Bonadio. - Bonadio, Enrico (Cambridge University Press, 2019)
In recent years, the number of conflicts related to the misuse of street art and graffiti has been on the rise around the world. Some cases involve claims of misappropriation related to corporate advertising campaigns, while others entail the destruction or 'surgical' removal of street art from the walls on which they were created. In this work, Enrico Bonadio brings together a group of experts to provide the first comprehensive analysis of issues related to copyright in street art and graffiti. Chapter authors shed light not only on the legal tools available in thirteen key jurisdictions for street and graffiti artists to object to unauthorized exploitations and unwanted treatments of their works, but also offer policy and sociological insights designed to spur further debate on whether and to what extent the street art and graffiti subcultures can benefit from copyright and moral rights protection.